Design and Implementation of a Contemporary Health Administration Program for Health Managers - Khalil, Hanan; Liu, Chaojie (Frontiers in Public Health, 2021)
Background: While there are core competencies required in health administration programs, little is known about how they are taught in health administration programs to support/change practises. This discussion paper describes an educational innovation to design a contemporary Master of Health Administration program to meet the current needs of health managers in Australia based on evidence-based practise. Method: A detailed gap analysis of health managers educational needs was undertaken with various stakeholders to design a contemporary health managers' program. Stakeholders surveyed in the course design included prospective students, international students' agencies, prospective employers, Alumni evaluation, mapping of health managers courses in Australia and faculty feedback. An integrative pedagogical approach was used to implement the program into action. Results: Various themes were emerged from the stakeholder consultations including the importance of basic knowledge of key subjects and the significance of learning new skills such as strategic planning and emotional intelligence in the workplace. The integrative pedagogical approach used is based on adult teaching principles, which were identified by Knowles. The subjects in the new course incorporate several knowledge-based presentations along with interactive activities, including use of general ability-based outcomes to define learning opportunities, case-based and problem-based learning, experiential learning, and comprehensive assessments. Conclusion: The results of this intensive consultation led to the design of a contemporary Master of Health Administration Course that included eight core subjects and multiple options of specialisations for students to choose from. Examples of specialisations include aged care and ageing, health promotion, data for decision making, public health, international development and Health Strategy and decision making.